Prediction of natural gas densities using equations of state of Soave-Redlich-Kwong, Peng-Robinson and AGA8-DC92 - Zavaleta Ortiz, Jack (2006)
In this work the Soave-Redlich-Kwong(SRK), Peng-Robinson (PR) y AGA8-DC92 (AGA) equations of state have been used to predict the density of different natural gas mixtures. AS a result, SRK and PR are strongly recommended for temperatures within the range 240-350 K. As for the pressure, SRK yielded better results within the range 1-8 MPa, whereas PR was more accurate for pressures ranging from 1 to 15 MPa. The errors obtained were smaller than 3% for all the 613 experimental point taken from the literature, which is convenient due to the fact that AGA is not easy to handle. Nevertheless, AGA displayed the best performance in every calculation and proved to be superior to either SRK or PR in the whole range of conditions used in this investigation. Finally, a computational tool has been developed to calculate density (ρ) and compressibility factor (Z). Such a tool incorporates an experimental database of ρ for different gas natural mixtures.